Bibliometric analysis of physics problem solving. Issue 1 (February 2021) - Ari Masitoh, Putri Nagres; Latifah, Sri; Saregar, Antomi; Aziz, Abdul; Suharto,; Jamaluddin, Wan
Abstract: Problem-solving in physics learning began to be researched in 2001. The bibliometric approach used in this study aimed to map the research literature on problem-solving in physics learning using Scopus as the metadata source. The downloaded database had been input into the VOSviewer software to be mapped. There were 52 analyzed articles taken from 24 leading journals from January 1 st, 2001 to August 31 st, 2020 (20 years period). The articles were written by 132 authors affiliated to 85 institutions in 16 countries. Indonesia was the most productive country. 91.7% of authors own 2 publications. From 4 reviewed clusters, the most frequently appeared keywords and topics are students, problem-solving, problem-solving skills, problem-solving abilities, and physics learning. the uncommon variables and have not been widely researched related to problem-solving in physics learning are presented along with future study opportunities.